Basic school teachers’ personality type as determinant of classroom management in Lagos State, Nigeria - Omoshalewa Lasbat Badamas (Intelektual Pustaka Media Utama, 2021)
Teachers encounter many problems in the classroom and amongst is classroom management. Classroom management pose a problem to teachers especially the novice teachers who are not privileged to undergo the training of teaching profession. Teachers’ personality type play an important role in whether to increase positive behaviours or decrease negative behaviours among the students in classroom environment. This study therefore examined teachers’ personality type as determinant of classroom management in Lagos State. Descriptive method of research was used for this study. The respondent comprised of 180 teachers selected from 15 schools in Lagos State. Two instruments were used in gathering data for the study. Mean rating and Pearson Product Moment Coefficient were used to answer and test research questions and hypotheses respectively. Findings revealed that teachers personality determines their classroom management.